Public health law in a nutshell - Hodge, James G. (Nutshell series, 2018)
Public Health Law in a Nutshell, 3rd Edition (2018) provides a fascinating and informative assessment of the critical role of law in American society to protect the community’s health. Understanding the field of public health law encompasses its constitutional sources and limits as well as historic and modern attempts to regulate in the interests of public health and safety. This Nutshell explains and addresses these issues within a modern framework supporting the role of law toward improved health outcomes. Updated to reflect key developments through mid-2017, the Nutshell’s 11 chapters and 130+ graphics, illustrations, and figures lay out definitive legal issues underlying core public health powers to prevent and control communicable and chronic conditions, as well as injuries and related deaths. It also explores legal routes to counter other public health threats, including tobacco and alcohol use, guns, vehicles, and defective products. Additional chapters center on difficult trade-offs related to public health information surveillance and privacy, commercial speech regulation, zoning and the built environment, and emergency legal preparedness. This Nutshell is a “must have” text for legal or public health practitioners in the field, law- and policy-makers seeking to protect the public’s health, and graduate students in schools of law, public health, or medicine, as well as undergraduates, assessing these issues as part of their coursework or research interests.